Real world Haskell - O'Sullivan, Bryan (O'Reilly, 2008)
"Real World Haskell is an easy-to-use, fast-paced tutorial that introduces you to this increasingly popular language. You'll learn how to use Haskell in a variety of practical ways, from writing short scripts to large and demanding applications. The basics of functional programming are introduced, helping you develop your understanding of how to use Haskell with real-world issues, such as I/O performance, dealing with data, concurrency, and more."--Jacket